Rausyan Fikr: Gerakan Intelektual Syiah di Yogyakarta - Syauqii, Fachri (Islamic Education, 2024)
Rausyan Fikr is a research institution that operates in the field of philosophy, particularly Islamic philosophy. Established by Romy Fibri and colleagues in 1995, Rausyan Fikr aims to enlighten students from various campuses. The name Rausyan Fikr itself is derived from Ali Syariati's concept, which refers to an intellectual who achieves enlightenment. The focus on philosophical studies responds to the intellectual fluctuations among students torn between Islamic and Western thought. Additionally, Rausyan Fikr houses a library and has branches for study, such as the Muthahhari Student Islamic Boarding School (PPM) and JAKFI (Islamic Philosophy Activist Network). This study is open to various groups, with increasing interest each year from students and academics in Islamic philosophy. The research methods employed are field studies and qualitative analysis. The theoretical frameworks used include social movements, social intellectuals, and their roles. The objective is to examine the influence of Islamic thought, particularly from Iranian thinkers, on academics and students in Indonesia, especially in Yogyakarta, near Kaliurang road.